Simulation and Analysis of Double Compound CAM Pusher Tool Changing Mechanism for NC Machine Tool - Xinbo Zhang; Xiaobing Zhang; Xigui Wang; Zhongping Lai; Wenxue Zhu; Yujie Zhang (Machines)
The core mechanism of existing CNC tool changers is typically a single composite cam swinging rod linkage. This setup has two main drawbacks: amplified vibration errors and high impact forces due to the swinging rod. To address these, this study focuses on CNC tool changers, specifically selecting the up-and-down motion follower and proposing a novel double composite cam push rod type mechanism. Solid modeling for both mechanisms was conducted using Creo and Matlab, and theoretical modeling of the contact forces for each follower type was completed. Comparative analysis shows the push rod follower exhibits lower contact forces than the swinging rod. Using the Adams platform, the dynamic characteristics of both mechanisms were analyzed, leading to an optimized design for the push rod type. An experimental model, scaled to 0.5, was built to compare experimental data with simulation results. The findings verify the accuracy of the models, supporting the feasibility of the push rod type tool changer.